Kinesiology : - Hamilton, Nancy (McGraw-Hill Higher Education, 2008)
This introductory text provides undergraduate students with the basics of anatomy, physiology, and the applications of kinesiology. It uses a qualitative approach with an easy-to-follow writing style. Theory is balanced with many sport and real-world applications to promote the integrated nature of kinesiology, including the anatomical and biomechanical concepts.